2013
DOI: 10.21101/cejph.a3796
|View full text |Cite
|
Sign up to set email alerts
|

Caries Prevalence in Chronic Alcoholics and the Relationship to Salivary Flow Rate and pH

Abstract: Aim: The aim of this study was to investigate the dental status of alcoholics; to evaluate the relationship of unstimulated and stimulated saliva pH on their decayed/missing/filled teeth (DMFT); and to evaluate the relationship of unstimulated and stimulated salivary flow rate on their DMFT. Method: A cross-sectional study was conducted in patients treated for alcohol dependency (n=70; mean age 41.7 years) and a control group of non-alcoholics (n=70; mean age 39.1 years). Examinations for dental caries were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…The volume of stimulated saliva was then measured as described for the unstimulated saliva above and the flow rate calculated. The obtained flow rates were divided in three categories: very low (<0.7 mL min -1 , as diagnostic criterion for hyposalivation), low (0.7-1.0 mL min -1 ), and normal (>1.0 mL min -1 ) (26,27). Salivary sCD14 secretion rates (ng min -1 ) were calculated from the saliva volume (mL) in one minute and the corresponding sCD14 concentration (ng mL -1 ).…”
Section: Saliva Collectionmentioning
confidence: 99%
“…The volume of stimulated saliva was then measured as described for the unstimulated saliva above and the flow rate calculated. The obtained flow rates were divided in three categories: very low (<0.7 mL min -1 , as diagnostic criterion for hyposalivation), low (0.7-1.0 mL min -1 ), and normal (>1.0 mL min -1 ) (26,27). Salivary sCD14 secretion rates (ng min -1 ) were calculated from the saliva volume (mL) in one minute and the corresponding sCD14 concentration (ng mL -1 ).…”
Section: Saliva Collectionmentioning
confidence: 99%
“…42 Enberg et al 43 also found significantly more caries and fewer teeth present in an alcohol dependent group, compared to a control group of social drinkers. However, Dukić et al 44 found no significant difference in the number of decayed, missing or filled teeth in alcoholics receiving treatment, compared to a control group. They did, however, report a lower unstimulated saliva flow rate and a lower pH of saliva in the alcoholic group.…”
Section: Wearmentioning
confidence: 96%
“…A cross sectional study conducted in India on alcohol dependency and oral health, reported that alcoholdependent subjects had slightly lower mean plaque and salivary pH, and a higher prevalence of dental caries, periodontitis and mucosal lesions, compared with nonalcoholic subjects 19 . Another study on the prevalence of dental caries in chronic alcoholics conducted in Eastern Europe reported no major differences in the prevalence of caries in alcoholics compared to the non-alcoholics group 20 . A 2015 study which explored smoking, alcohol use, socioeconomic background and oral health among young Finnish adults found that the consumption of alcohol was not associated with dental caries and periodontal disease 21 .…”
Section: Introductionmentioning
confidence: 92%